Assessing needs, fostering development: UNESCO, illiteracy and the global politics of education (1945–1960). Issue 1 (2nd January 2017) - Matasci, Damiano
ABSTRACT: In the aftermath of the World War II, United Nations Educational, Scientific and Cultural Organization (UNESCO) launched an ambitious campaign to improve access to education and to fight illiteracy worldwide. The Universal Declaration of Human Rights of 1948 had legitimised international action to raise educational and living standards in the 'underdeveloped' areas of the world, many of which were still under colonial rule. Based on primary archival material, this article sheds light on UNESCO's efforts to assess educational levels in these territories, notably by collecting, standardising and processing data and statistics. The analysis shows how the work UNESCO undertook to measure inequalities contributed to the reappraisal of the economic and social role of literacy thus laying the foundations of a number of pedagogical programmes designed for developing countries. The limits of UNESCO's global policies are also considered. Against the background of the Cold War and decolonisation, UNESCO's assessment of educational needs in colonial areas raised highly political problems, which significantly affected the global concern for the right to education.